Microtubules : In Vivo - Cassimeris, Lynne; Tran, Phong (Methods in cell biology ;, 2010)
Thisvolume includes chapters by experts around the world on many aspects of microtubule imaging in living and fixed cells; assays to study microtubule function in a wide array of model organisms and cultured cells; high resolution approaches to study of the cytoskeleton. The authors share their years of experience, outlining potential pitfalls and critical factors to consider in experimental design, experimental implementation and data interpretation. Iincludes chapters by experts around the world on many aspects of microtubule imaging in living and.